EarSketch: Engaging Broad Populations in Computing Through Music. - FREEMAN, JASON; MAGERKO, BRIAN; EDWARDS, DOUG; MCKLIN, TOM; LEE, TANEISHA; MOORE, ROXANNE (Communications of the ACM, 2019)
The authors reports on the use of the EarSketch music software to teach computer programming. They mention the ability of students to compose music,how the students changed their perceptions of computer programming, and the importance of programming in many career fields.